Reduced Nasal Nitric Oxide in Diffuse Panbronchiolitis - NAKANO, HITOSHI; IDE, HIROSHI; IMADA, MASANOBU; OSANAI, SHINOBU; TAKAHASHI, TORU; KIKUCHI, KENJIROU; IWAMOTO, JUN (American journal of respiratory and critical care medicine, 2000)
Diffuse panbronchiolitis (DPB) is a pulmonary disease of unknown origin with inflammation in the respiratory bronchioles, bronchiectasis, and recurrent sinusitis. Patients with DPB suffer from chronic airway infections resulting from mucociliary dysfunction. Whereas a high concentration of nasal nitric oxide (NO) has been documented in healthy subjects, only two diseases are known to reduce nasal NO: primary ciliary dyskinesia syndrome and cystic fibrosis. We hypothesized that patients with DPB have abnormal levels of nasal NO. To test our hypothesis, we measured NO with the chemiluminescence technique. Air was sampled directly from the nose in 15 healthy subjects and eight patients with DPB. Nasal NO was 88% lower in DPB patients than in the age-matched control subjects (69 +/- 70 versus 556 +/- 87 nl/min; p < 0.001). Treatment with erythromycin for 2 wk did not alter the nasal NO in four control subjects. DPB is the third pulmonary disease in which nasal NO is low. The reduced nasal NO may well be involved in the pathogenesis of DPB, and NO measurements may serve as a noninvasive test in the diagnosis of DPB.